PENGARUH BENTUK PROFIL GERMANIUM PADA FREKUENSI CUTOFF HBT SIGE - Julian, Engeline Shintadewi (Jurnal Teknik Elektro, 2003)
The effects of different shape of germanium profiles in the base to the cutoff frequency ofSi/SiGe/Si HBTs are analyzed. The shapes of germanium profile in the base are triangles. Inthe simulations, the effect of bandgap narrowing due to the addition of germanium in thebase of the HBT is included. The simulations are done with BIPOLE3V4.2.3.E. The resultsshows that Ge profiles in the base have influence in the maximum cutoff frequency of theHBTs.Keywords: SiGe, HBT, hetero junction bipolar transistor, frequency cutoff